Protein mannosylation as a diagnostic and prognostic biomarker of lupus nephritis: an unusual glycan neoepitope in systemic lupus erythematosus - Alves, Inês; Santos-Pereira, Beatriz; Dalebout, Hans; Santos, Sofia; Vicente, Manuel M.; Campar, Ana; Thepaut, Michel; Fieschi, Franck; Strahl, Sabine; Boyaval, Fanny; Vizcaíno, Ramon; Silva, Roberto; et al. (Arthritis & rheumatology, 2021)
Objective Changes in protein glycosylation are a hallmark of immune-mediated diseases. Glycans are master regulators of the inflammatory response and are important molecules in self-nonself discrimination. This study was undertaken to investigate whether lupus nephritis (LN) exhibits altered cellular glycosylation to identify a unique glycosignature that characterizes LN pathogenesis. Methods A comprehensive tissue glycomics characterization was performed in kidney specimens from patients with systemic lupus erythematosus and biopsy-proven LN. A combination of advanced tissue mass spectrometry, in situ glyco-characterization, and ex vivo glycophenotyping was performed to structurally map the repertoire of N-glycans in LN tissue samples. Results LN exhibited a unique glycan signature characterized by increased abundance and spatial distribution of unusual mannose-enriched glycans that are typically found in lower microorganisms. This glycosignature was specific for LN, as it was not observed in other kidney diseases. Exposure of mannosylated glycans in LN was shown to occur at the cell surface of kidney cells, promoting increased recognition by specific glycan-recognizing receptors expressed by immune cells. This abnormal glycosignature of LN was shown to be due to a deficient complex N-glycosylation pathway and a proficient O-mannosylation pathway. Moreover, mannosylation levels detected in kidney biopsy samples from patients with LN at the time of diagnosis were demonstrated to predict the development of chronic kidney disease (CKD) with 93% specificity. Conclusion Cellular mannosylation is a marker of LN, predicting the development of CKD, and thus representing a potential glycobiomarker to be included in the diagnostic and prognostic algorithm of LN.
Gesehen am 13.05.2022